Rattus rattus rattus (Linnaeus 1758 ... - Amr, Zuhair S.; Abu, Mohammad A.; Qumsiyeh, Mazin; Eid, Ehab (Zenodo, 2018)
Rattus rattus (Linnaeus, 1758) Common name: Black rat. Diagnosis: Ears large and rounded. Fur color very variable, ranging from blackish dorsally to grayish to brownish, with the underside being lighter (Figure 74). Head-body length up to 200 mm. Tail longer than head and body length. Little and short hair on tail. Large and well inflated tympanic bullae. Skull elongated in shape, with laterally curved tempoparietal ridges. Outer tubercles of upper molars well developed. First upper molar with anterolateral cusp (Figure 75). Localities: Found in all cities, villages and agricultural areas. Habitat: This is common species occurring in cities, villages and farming areas. Its populations are increasing rapidly in association with urban and agricultural expansion. The black rat successfully invaded remote areas in the country. Now it is well-established in farms in the Badia and southern Jordan. This was facilitated by vehicles transporting animal feed and other agricultural crops. Biology: Breeding takes place ... : Published as part of Amr, Zuhair S., Abu, Mohammad A., Qumsiyeh, Mazin & Eid, Ehab, 2018, Systematics, distribution and ecological analysis of rodents in Jordan, pp. 1-94 in Zootaxa 4397 (1) on pages 66-67, DOI: 10.11646/zootaxa.4397.1.1, http://zenodo.org/record/1202783 ...